2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091171
|View full text |Cite
|
Sign up to set email alerts
|

A continuous, wearable, and wireless heart monitor using head ballistocardiogram (BCG) and head electrocardiogram (ECG)

Abstract: Continuous and wearable heart monitoring is essential for early detection and diagnosis of cardiovascular diseases. We demonstrate a continuous, wearable, and wireless heart monitor that is worn at the ear. The device has the form factor of a hearing aid and is wirelessly connected to a PC for data recording and analysis. With the ear as an anchoring point, the heart monitor measures the ballistocardiographic (BCG) motion of the head using a MEMS tri-axial accelerometer, which is an electrode-less method to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…One is the pendular oscillatory motion that keeps the head in dynamic equilibrium. Like He et al [7], we found that the vertical direction is the best axis to measure the movement of the upright head caused by pulse because the horizontal axis tends to capture most of the dynamic equilibrium swaying. A second source of involuntary head movement is the bobbing caused by respiration.…”
Section: Head Movementsupporting
confidence: 66%
See 2 more Smart Citations
“…One is the pendular oscillatory motion that keeps the head in dynamic equilibrium. Like He et al [7], we found that the vertical direction is the best axis to measure the movement of the upright head caused by pulse because the horizontal axis tends to capture most of the dynamic equilibrium swaying. A second source of involuntary head movement is the bobbing caused by respiration.…”
Section: Head Movementsupporting
confidence: 66%
“…The net acceleration of involuntary vertical head movement has been measured to be around 10 mG (≈ .098 m s 2 ) [7]. The typical duration of the left ventricular ejection time of a heart cycle is approximately 1 3 seconds.…”
Section: Head Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not necessary to place the electrodes directly on the human organ e.g., over heart in case of ECG measurement. The attenuated ECG signal can be detected by placing the electrodes elsewhere e.g., behind the ear as demonstrated in [18,19]. If the human heart could be considered as a biomedical implant which is transmitting signals then the attenuated signals can be measured outside the body at a different location by a receiver.…”
Section: Introductionmentioning
confidence: 99%
“…In order to extract valuable information from the BCG signal, two approaches have been proposed: (1) to extract beat-by-beat series from short-duration (⩾3 min) recordings in order to characterize time and frequency parameters of heart-rate variability (Shin et al 2011, Zhu et al 2012; (2) to average consecutive beats acquired over shorter sequences (<1 min) in order to obtain a characteristic waveform from which to derive indices of cardiac performance (Etemadi et al 2011, He et al 2011.…”
Section: Introductionmentioning
confidence: 99%